PERAN HAKIM PERADILAN AGAMA DALAM MEWUJUDKAN KEADILAN DAN KEPASTIAN HUKUM MELALUI PUTUSAN - Hidayati Fitri (JURIS (Jurnal Ilmiah Syariah), 2018)
Pengadilan Agama (Islamic Civil Court) is a special judicial institution for civil matters since it is the responsibility of this institution to receive, check and solve particular problems among Moslems as it clearly stated in UU No. 5 Tahun 2009. Furthermore, dynamicity of the society should be the prior concern for the readiness of the personnels of the court in order that the any legal decisions made should be able to satisfy the justice values and ensure the law enforcement certainty.